Cationic conjugated polymer-based FRET aptasensor for label-free and ultrasensitive ractopamine detection. Issue 18 (7th April 2022) - Fu, Xuancheng; Dong, Wei; Liu, Chang; Han, Jing; Huang, Chengzhi
Abstract : A label-free fluorescence resonance energy transfer (FRET) platform based on cationic conjugated polymers and aptamer has established for ultrasensitive and specific ractopamine (RAC) detection. Abstract : A label-free fluorescence resonance energy transfer (FRET) platform based on cationic conjugated polymers and aptamers for ultrasensitive and specific ractopamine detection was constructed. This method exhibited a wide linear range from 0.05 to 500 μM and a low limit of detection of 47 nM, which make it an attractive assay platform for foodborne doping.